2019
DOI: 10.29399/npa.23539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functioning Levels and Associated Factors in Patients with Remission in Bipolar Disorder

Abstract: Introduction: The course of bipolar disorder (BD) is characterized by relapse and remission periods. Although the symptoms show a significant and sometimes almost complete improvement during remission, the patients' functioning levels may be lower compared to the premorbid period. This study aimed to compare the functional levels between patients with BD during remission period and healthy controls and to evaluate the factors related to the functional status of the patients. Methods: In this cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…BD often has an onset of symptoms during young age and may cause substantial functional impairments also before the time of diagnosis, and a progression of severity during years of untreated illness, stressing the need for early diagnosis and intervention [3][4][5]. An increasing focus has recently been on coexisting alterations in mood, activity and sleep, and loss of function, both during affective episodes, but also between affective episodes [6][7][8]. Currently, no objective biomarkers like blood tests or radiologic findings are available to diagnose or monitor BD.…”
Section: Introductionmentioning
confidence: 99%
“…BD often has an onset of symptoms during young age and may cause substantial functional impairments also before the time of diagnosis, and a progression of severity during years of untreated illness, stressing the need for early diagnosis and intervention [3][4][5]. An increasing focus has recently been on coexisting alterations in mood, activity and sleep, and loss of function, both during affective episodes, but also between affective episodes [6][7][8]. Currently, no objective biomarkers like blood tests or radiologic findings are available to diagnose or monitor BD.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the majority of studies follow hospitalized patients, who may be unrepresentative of the entire population (Angst, 2008;Rottenberg et al, 2018). For people with bipolar disorders, research has found that changes in depression severity are associated with functional impairment, whereas mania or hypomania symptoms are inconsistently associated with functioning (Hacimusalar & Dog ˘an, 2019;Simon et al, 2007). There are also indications that bipolar I produces greater functional impairment relative to other mood disorders ( Judd et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the majority of studies follow hospitalized patients who may be unrepresentative of the entire population (Angst, 2008;Rottenberg et al, 2018). For people with bipolar disorders, research has found that changes in depression severity are associated with functional impairment, while mania or hypomania symptoms are inconsistently associated with functioning (Simon et al, 2007;Hacimusalar & Doğan, 2019). There are also indications that bipolar I produces greater functional impairment relative to other mood disorders (Judd et al, 2008).…”
Section: Discussionmentioning
confidence: 99%